Penegakan Hukum Pidana Anak Sebagai Pelaku Perundungan dalam Perundang-Undangan di Indonesia - Rusmana, I Putu Edi (Wajah Hukum, 2024)
Children are the nation's next generation and play an important role in nation development. In life, children cannot be separated from perfection in terms of physical or mental life. These physical or mental deficiencies can become material for bullying by other children which can disrupt the child's survival and peace. In enforcing criminal law to stop bullying by children, the government issued Law Number 23 of 2002 concerning Child Protection, and amendments were made to Law Number 35 of 2014 concerning Child Protection to accommodate the increasing number of child crimes. The research method used is normative research which focuses on a legislative approach and a conceptual approach. After collecting the results of this research, it is then developed through an interpretive approach. The conclusion that can be drawn from this research is that bullying is any action or behavior carried out with the aim of causing injury. This harm can be physical, psychological, emotional, or verbal. Bullying behavior combines several criminal acts in the Criminal Code and for children using the Juvenile Criminal Justice System Act. The second conclusion is that children who are accused of bullying are threatened with criminal sanctions. According to the Juvenile Criminal Justice System Law, cases of bullying committed by teenagers can be brought to court and the judicial process will be carried out according to the law for children.